CONSUMER PURCHASE INTEREST BASED ON SOCIAL, ELECTRONIC WORD OF MOUTH AND IMAGE - Digan Zahroh Fadhilah,; Silaningsih, Endang; Yuningsih, Erni (Jurnal Visionida, 2024)
This study examines social media, electronic word of mouth (eWOM) and brand image both simultaneously and partially on consumer buying interest. The sampling technique used non probability sampling technique with purposive sampling method. The research sample was 100 respondents using the Lemeshow formula. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique uses descriptive verification analysis, validity and reliability tests, multiple linear tests and classical assumption tests. The results showed that both simultaneously and partially there was a positive and significant effect of social media, electronic word of mouth (eWOM), and brand image on purchase intention.